The Association between Periodontal Conditions and Serum Lipids among Elderly Participants in Gadjah Mada Medical Centre, Yogyakarta - Widita, Elastria; Hanindriyo, Lisdrianto; Widyaningrum, Rini; Priyono, Bambang; Agustina, Dewi (UI Scholars Hub, 2017)
Prevention of cardiovascular diseases by controlling risk factors at an early stage is very important. Objective: To determine the relationship between periodontal conditions with serum lipids among the elderly. Methods: Total of 78 participants (56 males and 32 females) who were in the age range of 60-76 years were selected for the current study. A logistic regression analysis was used to evaluate the association between periodontal conditions and serum lipid profile. Periodontal conditions was recorded as the maximum score of pocket depth (PD) and loss of attachment (LoA) score which presented in the participants, while levels of total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL), and triglycerides (TG) were measured for the serum lipids profile. Age, gender, BMI, high blood pressure, pattern of dental visit, hypertension and cholesterol medication, number of teeth, PD, and LoA were included in the model as independent variable. TC, HDL, LDL, and TG were used as dependent variables. Results: According to the results of the logistic regression analysis, loss of attachment >6 mm was associated with TC (p<0.01; 5.295(1.710-16.391) and LDL (p<0.05; 2.87(1.118-7.405), while PD had no association with serum lipids (p>0.05). Conclusion: This study indicates that subjects with greater loss of attachment significantly associated with higher levels of serum TC and LDL. This may suggest that elderly people with greater loss of attachment are potentially at risk of having serum lipid impairment.